Discriminant ability of the Eating Assessment Tool‐10 to detect aspiration in individuals with amyotrophic lateral sclerosis. Issue 1 (28th October 2015) - Plowman, E. K.; Tabor, L. C.; Robison, R.; Gaziano, J.; Dion, C.; Watts, S. A.; Vu, T.; Gooch, C.
Abstract: Background: Oropharyngeal dysphagia is prevalent in individuals with amyotrophic lateral sclerosis (ALS) leading to malnutrition, aspiration pneumonia, and death. These factors necessitate early detection of at‐risk patients to prolong maintenance of safe oral intake and pulmonary function. This study aimed to evaluate the discriminant ability of the Eating Assessment Tool (EAT‐10) to identify ALS patients with unsafe airway protection during swallowing. Methods: Seventy ALS patients completed the EAT‐10 survey and underwent a standardized videofluoroscopic evaluation of swallowing. Two blinded raters determined airway safety using the Penetration Aspiration Scale (PAS). A between groupsanova (safe vs penetrators vs aspirators) was conducted and sensitivity, specificity, area under the curve (AUC), and likelihood ratios calculated. Key Results: Mean EAT‐10 scores for safe swallowers, penetrators, and aspirators (SEM) were: 4.28 (0.79) vs 7.10 (1.79) vs 20.50 (3.19), respectively, with significant differences noted for aspirators vs safe swallowers and aspirators vs penetrators ( p < 0.001). The EAT‐10 demonstrated good discriminant ability to accurately identify ALS penetrator/aspirators (PAS ≥3) with a cut off score of 3 (AUC: 0.77, sensitivity: 88%, specificity: 57%). The EAT‐10 demonstrated excellent accuracy at identifying aspirators (PAS ≥6) utilizing a cut off score of 8 (AUC: 0.88, sensitivity: 86%, specificity: 72%, likelihood ratio: 3.1, negative predictive value: 95.5%). Conclusions & Inferences: The EAT‐10 differentiated safe vs unsafe swallowing in ALS patients. This patient self‐report scale could represent a quick and meaningful aide to dysphagia screening in busy ALS clinics for the identification and referral of dysphagic patients for further instrumental evaluation. Abstract : Mean (SEM) Eating Assessment Tool‐10 scores for ALS patients with safe swallowing (PAS<2), penetrators (PAS:2‐5) and aspirators (PAS>6). ALS aspirators EAT‐10 score was significantly higher (worse) then both safe swallowers and penetrators ( p <0.001).